Correlation between colposcopic impression using Reid’s colposcopic Index and histopathological grading of premalignant lesions of cervix - S., Raksha; Mishra, Nigamananda; Savani, Gayatri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cancer cervix is in the top rank of gynecological cancers in the developing countries cervical cancer has a long latent period and can be prevented by simple treatment of cervical intraepithelial neoplasm. The incidence of invasive cancer can be decreased by early detection of preinvasive stage which can be treated at the same sitting, “see & treat approach” strategy. Objectives were to estimate the strength of correlation in detecting preinvasive lesions of cervix between colposcopy and directed biopsy and to correlate various socio-demographic data with cervical pre-invasive and invasive lesion. To compare the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy with colposcopic directed biopsy. Methods: On selecting the patients based on the criteria, per speculum examination was done and in the presence of abnormal cervix, advised for PAP smear. Based on PAP smear scaled according to Bethedsa staging, patients were accordingly advised for colposcopy. Reid’s colposcopic index applied and biopsy was taken over the site with highest score and sent for HPE in a labelled bottle with fixative. Results: Colposcopy when compared to histopathology had a sensitivity of 100 %, specificity of 48.3%, with PPV of 22.4 % and NPV of 100 %. The p value was 0.001 suggesting a significant strength of agreement between colposcopic diagnosis using Reid’s index and histopathological diagnosis. Conclusions: Correlation of colposcopic impression with directed biopsy is described as the reference investigation or ‘gold standard’ for the diagnosis of cervical precancerous lesions.